Italy : Detailed Assessment of IAIS Insurance core Principles. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses the findings of Detailed Assessment of International Association of Insurance Supervisors (IAIS) insurance core principles on Italy. Regulation and supervision of the insurance industry in Italy is the responsibility of the newly established Institution for the Supervision of Insurance (IVASS). IVASS has reached international best practice in several areas of supervision. IVASS actively exercises group supervision and by 2000, IVASS established the first college of supervisors. Intragroup transactions and related party participations limits are strictly monitored and enforced. IVASS handling of the licensing of undertakings is complete and comprehensive and ensures appropriate considerations pursuant to regulations. Enhanced supervision in some areas is required.